Is Closed Reduction and Percutaneous Fixation of Unstable Posterior Ring Injuries as Accurate as Open Reduction and Internal Fixation?. Issue 1 (January 2016) - Lindsay, Adam; Tornetta, Paul; Diwan, Amna; Templeman, David
Abstract : Objectives: The objective of this retrospective review was to determine whether a closed reduction technique for unstable pelvic ring injuries is as accurate as an open technique. Design: Retrospective review. Setting: Two academic Level 1 trauma centers. Patients/Participants: We reviewed the records of 113 patients who had unilateral unstable pelvic ring injuries (Bucholz type 3, OTA type 61-C1) treated with closed reduction and percutaneous fixation (CRPF) or open reduction with internal fixation (ORIF). Intervention: Sixty patients were treated at one institution with open reduction and percutaneous iliosacral screw fixation. This involved prone positioning and a gluteus maximus sparing approach for direct visualization and reduction of the fracture. A second cohort of 53 patients was treated at a separate institution with closed reduction and percutaneous iliosacral screw fixation. This involved supine positioning and skeletal traction. Main Outcome Measures: Preoperative and postoperative plain radiographs of the pelvis were reviewed and standardized measurements were made to compare quality of reduction. Results: We were able to measure displacement within 0.1 mm. Overall reduction quality was slightly better for the CRPF group. The largest average difference in postoperative displacement was seen at the iliac wing height on anteroposterior pelvis radiographs with 6.3 mm (range 0–19.6) in the ORIF group versus 1.9 mm (range 0–4.7) in the CRPF group. Conclusions: The closed reduction technique described here is as effective as the ORIF technique in obtaining reduction of unstable pelvic ring injuries (Bucholz type 3, OTA type 61-C1). Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.